Innovative development in Ukraine: trends and problems - Гринько, Тетяна Валеріївна (Technology audit and production reserves, 2013)
The article discusses the problems of innovative development of Ukraine and analyzes the results of innovative activity, which identify the most urgent problems and obstacles that hinder the innovative development of the economy and the formation of the innovative model of development. Despite the large number of publications on the subject, today there is no any systematic approach to the solution of the problems of the innovative development. The article aims to explain contemporary problems of the innovative development of Ukraine and to develop trends of their solutions based on the analysis of results of the innovative activity in the country. The analysis helped to identify the priority problems of the innovative development and to ground the directions of their solutions. In Ukraine, the achievement of the benefits of the innovation economy depends on the effectiveness of the innovation breakthrough policy, which is based on the reformation of education, science, innovation activity, on the basis of the available scientific and technical potential with the world trends of scientific and technological development. The results can be applied when evaluating the innovative progress of developing countries, as well as when developing the effective mechanisms of functioning of the institutional infrastructure of the innovative development of the Ukrainian economy. A reasonable solution of problems of the innovative development in Ukraine will increase the level of the innovative development and the competitiveness; will permit to switch over to the innovative model and to become a full member of the world market in the near future.